Mathematical model for the integrated portable temperature calibrator unit system - Nurfaezah Norahim (2017)
Thermistors are type of temperature sensor which are commonly used in heat ventilation air-condition (HVAC) system. For example, they are utilized in air-condition (AC) unit to detect the temperature and send resistance signal to the AC module so that the system can adjust accordingly to maintain at the right temperature [1]. It serves as a negative feedback of the control system. Some thermistors are installed in a position near a heating unit and the thermal radiation affects the performance of the thermistor to provide an accurate temperature reading. Therefore, it is important for the engineer or technician in-charge of maintaining the AC system to send the thermistors for calibration. Calibration is a process to validate the true performance of the thermistor. Usually, the thermistors are sent to authorized laboratory to be calibrated. Even though the procedure in laboratory gives accurate results of the thermistors due to the advance facilities, it takes a lot of time for the thermistors to be returned and utilized in the AC unit which is on hold. It is unfavourable to keep the AC unit on hold for too long especially if it is for an urgent use. Therefore, an integrated portable temperature calibrator unit is designed as an alternative to calibrate the thermistor instead of sending them to the laboratory. It aids in time consumption and cost reduction in calibrating the thermistors. The portable calibrator unit needs to be reliable and provide accurate results of the performance of the thermistors. One of the factors that makes the portable calibrator unit accurate is the mathematical model of the system which is the focus of this project. Steinhart-Hart equation is a common equation used in calibration which shows the relationship between temperature and resistance. Two methods explored to solve for the unknown coefficients of the equations are QR factorization and least square method. Among the two methods, the least square method is more practical than QR factorization to be used in the portable calibrator unit for its less complexity Another method explored to prove the reliability of Steinhart-Hart equation is inverse calibration equation.